DEVELOPMENT OF LANDSCAPE GENRE IN NATIONAL PAINTING - Avazjon Shuhratugli Abdumajitov (Galaxy International Interdisciplinary Research Journal, 2023)
In the article, the role of the landscape genre in the work of young artists in the visual arts of Uzbekistan, the creative works of the landscape artist O. Tansikboyev are analyzed in detail.